2007
DOI: 10.1111/j.1744-6198.2007.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Said Another Way Subject Matter Experts: Facts or Fiction?

Abstract: Subject matter experts (SMEs) can be valuable resources, but there are no standards or criteria for their selection. The temptation to assert one's self as an SME in the absence of actual expertise is great. As a consumer, where does one turn, how does one know who to believe, and where does one place trust? What constitutes an SME is explored using two methods of how SMEs are developed. The reader is guided through finding, selecting, and validating an SME. The identification of some obstacles in using SMEs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The inter‐rater reliability in this study was evaluated by the use of ICC and showed no difference between the assessors. This demonstrated that the methodology used to construct the marking schemes was effective and efficient both in allowing accurate assignment of a score for the assessment items, while allowing markers to demonstrate their expert status [21]. Another important facet of assessment construction is generalizability (G) theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inter‐rater reliability in this study was evaluated by the use of ICC and showed no difference between the assessors. This demonstrated that the methodology used to construct the marking schemes was effective and efficient both in allowing accurate assignment of a score for the assessment items, while allowing markers to demonstrate their expert status [21]. Another important facet of assessment construction is generalizability (G) theory.…”
Section: Discussionmentioning
confidence: 99%
“…The SME panel members then used an iterative process to write and review the assessments and the marking schemes. The varying levels of clinical experience brought by the SME allowed them to gauge the level/difficulty of the questions, as well as associating them with current in‐hospital practice [21]. Through this process the items were set at a level the panel felt a junior doctor should be able to achieve.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the SMEs had more than 20 years of service in the police force. Instructors attached to the training wing occupied this role based on their knowledge of police tactics and their ability to observe and guide colleagues (see Lavin et al, 2007 , for a critical discussion of the use of SMEs). The leaders of the training wing were also involved in designing the study, including the variables used.…”
Section: Methodsmentioning
confidence: 99%
“…Coastal. Lavin, R., Dreyfus, M., Slepski, L., Kasper, C. (2007). Said another way: subject matter experts: facts or fiction?…”
Section: E 33mentioning
confidence: 99%